2020
DOI: 10.1093/joc/jqaa031
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Incidental Exposure to Political Information in Online Environments

Abstract: This article aims to explain learning outcomes of incidental exposure (IE) to political information in online environments. Drawing on the Political Incidental News Exposure Model, we predict learning outcomes by distinguishing between first-level (i.e., scanning of incidentally encountered information) and second-level IE (i.e., effortful processing of incidentally encountered information appraised as relevant). Furthermore, we conceptualize intention-based IE (i.e., while looking for non-political content) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…An early study on how online incidental news exposure impacts political knowledge found that incidental exposure educates the public about political affairs (Tewksbury et al, 2001). More recently, Nanz and Matthes (2020) reported that incidental exposure increases knowledge when individuals effortfully process the encountered information instead of just scanning it.…”
Section: Serendipitous Exposure and Social Mediamentioning
confidence: 99%
“…An early study on how online incidental news exposure impacts political knowledge found that incidental exposure educates the public about political affairs (Tewksbury et al, 2001). More recently, Nanz and Matthes (2020) reported that incidental exposure increases knowledge when individuals effortfully process the encountered information instead of just scanning it.…”
Section: Serendipitous Exposure and Social Mediamentioning
confidence: 99%
“…Third, in addition to non-incidental exposure, people may also experience incidental exposure to political news (Nanz & Matthes, 2020). With the wide use of social media, people are often unconsciously and passively exposed to political news.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Adreas and Mathes [14], this exposure to news can be distracting and can cause people to waste time contemplating over frivolous news. Frank & Pero [12] express that such exposure to news can cause aversion to it.…”
Section: Introductionmentioning
confidence: 99%